2015
DOI: 10.1186/s12955-015-0296-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing children’s interpretations of the Aboriginal Children’s Health and Well-Being Measure (ACHWM)

Abstract: BackgroundThere are emerging opportunities to improve the health of Aboriginal children and youth. The Aboriginal Children’s Health and Well-being Measure (ACHWM) was developed to enable Aboriginal communities to obtain group-level data from the perspectives of their children 8 to 18 years of age. The survey was developed in collaboration with children, based on the Medicine Wheel framework. The purpose of this study was to ensure that children and youth interpreted the ACHWM questions consistently and accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…The measure has four quadrant scores, representing the four directions of the medicine wheel. The validity and reliability of the ACHWM have previously been established, [13][14][15] as has its relevance to other Aboriginal communities in Ontario. [16][17][18] The objective of this paper is to describe the ACHWM screening process and evaluate its effectiveness.…”
mentioning
confidence: 99%
“…The measure has four quadrant scores, representing the four directions of the medicine wheel. The validity and reliability of the ACHWM have previously been established, [13][14][15] as has its relevance to other Aboriginal communities in Ontario. [16][17][18] The objective of this paper is to describe the ACHWM screening process and evaluate its effectiveness.…”
mentioning
confidence: 99%
“…It is widely agreed that developmental screening instruments designed in Western countries are not necessarily valid for children throughout the world . The use of these tools in Indigenous contexts is not culturally appropriate and is likely to lead to inaccurate results that are unhelpful and may be harmful . Respondents in our study shared these concerns; they reported that ad hoc modifications were often made, such as omitting items from the ASQ‐3 due to parents' difficulty understanding, leading respondents to question the ASQ‐3 accuracy.…”
Section: Discussionmentioning
confidence: 88%
“…Scores range from 0 to 100 and higher scores indicate better health. In addition to being culturally appropriate (Young et al, 2013;Young, Wabano, Ritchie, et al, 2015), it is also valid (Young, Wabano, Ritchie, et al, 2015;Young, Wabano, Usuba, et al, 2015) and reliable . In the hands of First Nations health leaders, the ACHWM process enables solutions to come from within each community (Saylor & Blackstock, 2005) and fosters empowerment (Chandler & Lalonde, 2009).…”
Section: The Aboriginal Children's Health and Well-being Measure (Achmentioning
confidence: 99%
“…The screening tool embedded within the Aboriginal Children's Health and Well-being Measure (ACHWM) 6 is a strategy for earlier identification. The ACHWM was developed by Aboriginal children and health providers, in collaboration with academic researchers (Young et al, 2013;Young, Wabano, Ritchie, et al, 2015;Young, Wabano, Usuba, et al, 2015). It is completed independently by children (8 to 18 years), using Android tablets.…”
Section: Introductionmentioning
confidence: 99%